TRAVELOKA AS THE ULTIMATE WORKPLACE FOR MILLENNIAL GRADUATES IN INFORMATION AND TECHNOLOGY - Fransisca Maria Harita; Teguh Priyo Sadono; Meta Sya; Joshua Fernando; Jai Kishon Goswami (ASPIRATION Journal, 2020)
Traveloka is one of the online agents for booking airline tickets, hotels, trains, and several other online services. Traveloka is one of the Unicorns from 4 startup businesses in Indonesia. Unicorn is a term for startups worth over the US $ 1 billion or equivalent to Rp. 13.5 trillion. Traveloka is an organization that applies advanced organizational communication; in structural and transitional theory, the structure is seen as a hierarchy, policy, and organizational design, whereas Weick views structure as an activity and, more specifically, as a communication activity. According to the concept of Weick, humans do not only run organizations; humans are these organizations. This study discusses the understanding of the meaning shared by Traveloka employees about the organization where they currently work. This shared understanding was obtained from the interaction between Traveloka employees. Convergence theory developed by Ernest G. Borman is used to find out how the process of awareness of groups or organizations is formed, developed, and survived. The research uses qualitative methods and constructivist paradigms. The results of the study show that there is a message dramatization process that forms a type of fantasy chain about Traveloka as an organization where competent people are especially in the field of Information and Technology (IT), and as an organization that is Flexible & Responsible. From the results of interviews with six informants who are Traveloka employees, the researchers obtained four points in common with their basic values ​​as part of the Traveloka organization, which directs them to Traveloka employees as the ultimate end.